REDRUM - Anidjar, Gil (Method & theory in the study of religion, 2019)
This essay is a response to readers and discussants with regard to Blood and to the limits and origins of Christianity. Deploying the Derridean idiom of mark and context, the singularity of blood in Christianity, of Christianity in its relation to blood, is what is here reiterated